ETR 300 : Pusat Muzik Irama / Nurul Naim Muhammad ... [et al.] - Muhammad, Nurul Naim; Harudin, Syahmi; Mohd Nasir, Mohd Farid; Azizi, Mohd Faris; Azhar, Azizul Azmi (2001)
In the millennium era and as a new business that being set up in the business world, we all agreed to choose "PUSAT MUZTK IRAMA" as our company's name. Five members involve in forn1ed up this company. The reason why we choose this name is to make public by nature know what type of our business and this indirectly can act as part of our business promotion. We also choose this name to show our company committed with this business and want to serve the best and excellent service to our customer. We have agreed to operate our business at Pekan Baru, Sungai Petani, Kedah. The reason why we choose this location is because its very suitable place and from our research there is no other competitors at this place so, the chance for our business to develop is bright. These places also become our target market. This company main business is selling musical instruments and services it, also serve musical courses. Beside that our business serve a service like sound and lightning stage installation and jamming studio. We are very positive in running this business because the demand for this business according to our research is rising and there is only a few company involve with this business. Our target market for general is for the people around the age of eight till twenty. For specified is for the student primary and secondary school at Sungai Petani and colleges such as Universiti Teknologi Mara (UiTM), lnstitut Kemahiran Mara (1KM) and Maktab Perguruan Sultan Abdul Halim (MPSAH).Our business parallel with the government objective to encourage more bumiputra involve in the world of business and serve a service that can benefits public. Therefore we predict that this business have a good potential to be successful in the future and also make a huge benefits for the company itself and other profits.